Laparoscopic left liver lobectomy for hepatocellular carcinoma in a cirrhotic patient: a video report - Levi Sandri, Giovanni Battista; Vennarecci, Giovanni; Santoro, Roberto; Lepiane, Pasquale; Colasanti, Marco; Ettorre, Giuseppe Maria (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
We present a video case of a 51-year-old man admitted to our surgical and liver transplantation unit for hepatocellular cancer (HCC). Patient has a HCV cirrhosis with portal hypertension and esophageal varices F1. Child Pugh score was B7 and model of end staged liver disease (MELD) was 11. Body mass index (BMI) was 26.7 and ASA score was 2. No previous abdominal surgery. According with our multidisciplinary group we suggest a laparoscopic left lobectomy for the patient. Pringle manoeuvre was not performed. Operation time was 193 min and blood loss estimation was 100 cc. No transfusion was required. Postoperative course was uneventful, grade I of Clavien-Dindo Classification. Patient was discharged in day 8. In our experience laparoscopic resection in cirrhotic liver should be performed in selected patients and in an experienced team.